Perception Towards Nursing And It’s Futuristic Career Prospects Among Nursing Students At Selected Colleges - Vibha, Vibha; Kaur, Amandeep; kesar, Ashu; Varinda, Varinda; Kaur, Taranpreet; Kaur, Gurleen; Kaur, Taranveer; Kumari, Veena (Journal of Neonatal Surgery, 2025)
Background: Nursing is a healthcare profession that is focused on the care of individuals, families, and communities; so that they can attain, maintain, or recover optimum health. It is rated as one of the most trusted professions in the healthcare industry and is considered an exciting and in-demand profession. Nurses are 2/3rds of the health workforce in India Nursing students’ perception of nursing might have an impact on their self-concept, self-esteem, recruitment, retention, and performance. Aim: The aim of the study is to assess the perception of nursing and its futuristic career prospects among nursing students of selected colleges of Punjab. Materials and Methods: A quantitative non-experimental descriptive research approach and design was used to assess the perception of nursing and its futuristic career prospects among 200 nursing students who were selected by stratified probability sampling technique. Data was collected by using self-structured tool on perception towards nursing and futuristic career prospects. Results: The results of the study concluded that the majority of nursing students have a good perception towards nursing 71.5%, followed by 27% with have average level of perception, and a minimum number of students have a poor level of perception 1.5%. The majority (62%) of the nursing students wanted to move abroad after completing graduation in nursing. A maximum number of students (67%) agree that nursing is a financially secure career than any other profession. Conclusion: The study concluded that most of nursing students have good perception of nursing as a profession